Notes on the Combat Scene on Tang-e Sarvak III rock relief - Skupniewicz, Patryk N. (Acta Archaeologica Lodziensia, 2021)
The article examines the Parthian rock relief Tang-e Sarvak III from two perspectives: as a source of information on the military equipment, and as representation of the victorious mounted combat genre in ancient Iranian art. As a result of this analysis of the military equipment a picture emerges of a the warrior dressed in a metallic cuirass with central opening, a scale gorget of the old, Achaemenid style, segmented sleeves and lamellar trousers or leggings. His horse is barded in a lamellar caparison, with a longer apron in front which covers mount’s chest and partially his legs. The warrior has the archery equipment typical for the late Parthian period, which strongly differs from early Parthian and Sasanian archery equipment. In the course of an analysis of the form of the composition, several possibilities of reconstruction of the missing part of the relief have been proposed. At the same time, the possibility of a large battle scene with a multitude of participants has been excluded as not matching the visual language of the era